Case Studies on Finite Element Modeling of Welded Joints - Heinemann Patrick; Isopescu Dorina; Maxineasa Sebastian George (Bulletin of the Polytechnic Institute of Jassy: Constructions, Architechture Section, 2021)
Joints made out of tubular steel members are often used in industrial constructions, like offshore, trusses or tree-shaped columns. The joint area is the weakest point in a truss structure. Beside the normal static behaviour many non-linearities due to the geometry or to the welding process have to take into account. Steel hollow sections are often used. Much research was made on welded nodes so far, but mostly it is valid for limited geometries or load cases. A review of the main aspects in designing welded nodes are given.